Green synthesis of silver nanoparticles using neem and collagen of fish scales as a reducing and stabilizer agents - Mudhafar, Mustafa (Tanjung Malim, 2021)
Green synthesis of silver nanoparticles using neem and collagen of fish scales as a reducing and stabilizer agents by Mudhafar, Mustafa